Growth, development and morphology of gametophytes of golden chicken fern (Cibotium barometz (L.) J. Sm.) in natural media - TITIEN NGATINEM PRAPTOSUWIRYO; DIDIT OKTA PRIBADI; RUGAYAH RUGAYAH (Society for Indonesian Biodiversity, 2015)
Praptosuwiryo TNg, Pribadi DO, Rugayah. 2015. Growth, development and morphology of gametophytes of golden chicken fern (Cibotium barometz (L.) J. Sm.) in natural media. Biodiversitas 16: 303-310. The golden chicken fern, Cibotium barometz (L.) J.Sm., is an important export commodity for both traditional and modern medicine. To understand the reproductive biology of thisspecies, spore germination, gametophyte development, morphological variation, and sex expression were studied by sowing spores onsterilized natural media consisting of the minced roots of Cyathea contaminans and charcoaled rice husks (1: 1) mix. Spores ofC. barometz are trilete, tri-radially symmetrical, non chlorophyllous, and golden-yellow with a perine. Six stages of gametophytedevelopment (rhizoid stage, rhizoid/protochorm stage, filament stage, spatulate stage, young heart stage, mature heart stage) wereobserved between 24-45 days after sowing. Spore germination of C. barometz is Vittaria-type. Prothallial development of C. barometz isDrynaria-type. Five morphological types of adult gametophyte were recorded: (i) irregular spatulate shape (male), (ii) fan shape (male),(iii) elongated heart-shape (male), (iv) short heart or butterfly shape (female), and (v) normal heart shape (bisexual). The presence ofmorphological variations is presumed to be related to the population density, which significantly affects the sexual expression ofgametophytes. The variation of sex expression in C. barometz also indicates that this species may has a mixed mating systems thatresulted in genetic diversity within population and among populations.